Development and validation of stability indicating RP-HPLC method for simultaneous estimation of Ibuprofen and Carisoprodol in Pharmaceutical formulation - A Lakshmana Rao; P Vijetha (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2019)
A novel, rapid, precise and accurate stability indicating RP-HPLC method was developed and validated for the simultaneous estimation of Ibuprofen and Carisoprodol in combined pharmaceutical formulation. Chromatographic separation was achieved on Kromasil C18 column (250×4.6mm, 5μm) with UV detection at 260nm. The mobile phase consisting of 0.1% Ortho Phosphoric Acid (OPA) and acetonitrile in a ratio of 40:60v/v and adjusted the fl ow of mobile phase to 1.0mL/min.